PENINGKATAN AKSESIBILITAS UMKM DESA LIMA LARAS DENGAN OPTIMALISASI GOOGLE MAPS DALAM MENDORONG PERTUMBUHAN EKONOMI - Zahra Zeinatha Osya Simangunsong; Rizky Pratiwi; Norma Dianita; Nur'ain Harahap; Abdillah Asyraf Arbie (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aims to enhance the accessibility and visibility of UMKM in Lima Laras Village through the optimization of Google Maps. Most local businesses still rely on conventional promotional strategies, making them less recognized in the digital sphere. The study employed a four-cycle approach consisting of mapping, planning, implementation, and evaluation. The results show that three partner UMKM were successfully registered on Google Maps, enabling their business profiles to be more easily accessed by consumers. The SWOT analysis identified student involvement and the utilization of Google Maps as the main strengths, while the limitations of resources and low digital literacy remained challenges. On the other hand, the increasing use of the internet provides opportunities to expand market reach, although technological dynamics and digital competition continue to pose threats. Overall, Google Maps optimization proved effective in strengthening MSMEs’ marketing strategies. However, sustainable commitment from business owners and continuous support through digital assistance are needed to ensure long-term benefits and contribute to local economic growth.